Perovskite solar cell module with high conversion efficiency
Patent Information
- Application Number
- CN202610992438.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-06
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2046-07-06
AI Technical Summary
例如,金属电极在P2划线区域的扩散会加速钙钛矿层的降解;在P3划线过程中为去除金属电极会使用更高的激光能量,金属受热可能会氧化,增大了与相邻膜层或TCO层的接触电阻
[0016]1、本发明采用ITO/金属/ITO复合电极结构,利用介质层对金属层的物理包覆作用,有效抑制了金属在高温环境下的表面氧化反应;在此基础上,通过将不透明电极优选设置为底电极,顶电极为纯ITO等透明电极,可避免在P3划线工艺中对金属层进行直接烧蚀;该优选方案彻底阻断了高能量激光与金属的相互作用,杜绝了金属氧化的风险,消除了金属氧化物界面层增大接触电阻及诱发肖特基势垒的隐患;同时,由于金属层被ITO介质层隔离,显著降低了激光热冲击对邻近钙钛矿层的晶格热扰动与化学降解,减少了微裂纹萌生,有助于降低串联电阻、减小“死区”电学损耗,提升组件的效率绝对值;
Smart Images

Figure CN122514133B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a high-conversion-efficiency perovskite solar cell module, belonging to the field of perovskite / organic solar cell technology. Background Technology
[0002] Organic-inorganic hybrid perovskites have become one of the most promising semiconductor materials in recent years due to their high absorption coefficient, long carrier diffusion length, and tunable bandgap. Currently, the champion power conversion efficiency for small-area perovskite solar cells has reached 26.95%. However, significant efficiency losses occur when the device area is scaled up to module size. To date, perovskite solar modules (areas exceeding 100 cm²) have achieved limited efficiency. 2 The highest certified efficiency is 22.46%. The best modules can only operate stably for a few thousand hours, which is far behind silicon solar modules (10-30 years), seriously hindering the commercialization process.
[0003] The efficiency and stability of the module are significantly lower than those of small-area cells with similar structures. This is mainly because the series connection of multiple sub-cells in the module relies on laser scribing at P1, P2, P3, and P4. Laser scribing introduces several instabilities during the fabrication of perovskite modules with sputtered large-area metal electrodes. For example, the diffusion of the metal electrode in the P2 scribing region accelerates the degradation of the perovskite layer; higher laser energy is used to remove the metal electrode during the P3 scribing process, and the heated metal may oxidize, increasing the contact resistance with adjacent films or TCO layers. Furthermore, higher laser energy causes more significant thermal damage, leading to significant chemical degradation of adjacent perovskites and compromising the structural integrity of the film around the P3 scribing region; stress mismatch exists between the sputtered metal electrode and adjacent films, which can easily lead to metal film detachment or edge breakage during the P4 edge cleaning process. These instabilities directly affect the absolute efficiency and stability of the perovskite module. Summary of the Invention
[0004] The present invention aims to solve the above-mentioned problems, thereby providing a perovskite solar cell module with high conversion efficiency.
[0005] The technical solution of the present invention to solve the above problems is as follows:
[0006] A high-efficiency perovskite solar cell module includes a substrate, a first electrode, a first charge transport layer, a perovskite absorber layer, a second charge transport layer, and a second electrode stacked sequentially. The first electrode and the second electrode have opposite polarities. One of the first electrode and the second electrode is a transparent electrode, and the other is an opaque electrode. The first charge transport layer is an electron transport layer or a hole transport layer that matches the work function of the first electrode. The second charge transport layer is an electron transport layer or a hole transport layer that matches the work function of the second electrode.
[0007] To address the problems mentioned in the background section, the inventors adjusted the bottom and top electrodes. An opaque electrode film serves as the bottom electrode, while the top electrode uses a simpler and more stable transparent electrode, such as a pure ITO electrode. Light enters from the top electrode, is reflected upon reaching the bottom electrode, and then generates electricity. This approach avoids the direct sputtering of large-area metal electrodes, thus avoiding some adverse effects during laser scribing (such as metal electrode diffusion in the P2 scribing region, metal oxidation during P3 scribing, high-energy thermal damage, stress mismatch, etc.), indirectly optimizing the laser scribing effect and improving the absolute efficiency and stability of the perovskite module.
[0008] As a preferred embodiment of the above technical solution, the transparent electrode is an ITO electrode; the opaque electrode is a composite electrode, comprising a first ITO transparent layer, a metal layer, and a second ITO transparent layer, wherein the metal layer is disposed between the two ITO transparent layers.
[0009] As a preferred embodiment of the above technical solution, the metal layer is made of silver or copper.
[0010] As a preferred embodiment of the above technical solution, the thickness of the first ITO transparent layer and the second ITO transparent layer is 20~50nm, and the thickness of the metal layer is 50~100nm.
[0011] As a preferred embodiment of the above technical solution, the first electrode is an opaque positive electrode; the first charge transport layer is a hole transport layer; the second electrode is a transparent negative electrode; the second charge transport layer is an electron transport layer; and in use, light is incident from the side of the second electrode.
[0012] As another preferred embodiment of the above technical solution, the substrate is a transparent substrate; the first electrode is a transparent negative electrode; the first charge transport layer is an electron transport layer; the second electrode is an opaque positive electrode; the second charge transport layer is a hole transport layer; in use, light is incident from the transparent substrate side.
[0013] As another preferred embodiment of the above technical solution, the first electrode is an opaque negative electrode; the first charge transport layer is an electron transport layer; the second electrode is a transparent positive electrode; the second charge transport layer is a hole transport layer; and in use, light is incident from the side of the second electrode.
[0014] As a final preferred embodiment of the above technical solution, the substrate is a transparent substrate; the first electrode is a transparent positive electrode; the first charge transport layer is a hole transport layer; the second electrode is an opaque negative electrode; the second charge transport layer is an electron transport layer; and in use, light is incident from the transparent substrate side.
[0015] In summary, the present invention has the following beneficial effects:
[0016] 1. This invention employs an ITO / metal / ITO composite electrode structure, utilizing the physical coating effect of the dielectric layer on the metal layer to effectively suppress the surface oxidation reaction of the metal under high-temperature conditions. Furthermore, by preferably setting the opaque electrode as the bottom electrode and the top electrode as a transparent electrode such as pure ITO, direct ablation of the metal layer during the P3 scribing process can be avoided. This preferred solution completely blocks the interaction between the high-energy laser and the metal, eliminating the risk of metal oxidation and the potential for increased contact resistance and the induction of a Schottky barrier due to the metal oxide interface layer. Simultaneously, because the metal layer is isolated by the ITO dielectric layer, the lattice thermal disturbance and chemical degradation of the adjacent perovskite layer caused by laser thermal shock are significantly reduced, minimizing microcrack initiation, which helps to reduce series resistance, decrease "dead zone" electrical losses, and improve the absolute efficiency of the component.
[0017] 2. Because the metal layer is sandwiched between the two ITO transparent layers, it forms a dense physical and chemical barrier, effectively blocking the diffusion path of metal atoms (such as Cu, Ag, etc.) along the grain boundaries. Compared with the structure in the prior art where the metal electrode is directly exposed to the perovskite interface, this coating structure can suppress the thermal migration and ion diffusion of metal atoms under high temperature and built-in electric field, thereby slowing down the formation of deep-level defect states induced by metal impurities, blocking non-radiative recombination channels, delaying the phase separation and degradation of the perovskite layer, and significantly extending the working life of the component.
[0018] 3. To address the issue of interfacial stress concentration caused by Young's modulus mismatch and thermal expansion coefficient differences between metal electrodes and adjacent film layers in traditional structures, this invention utilizes an ITO / metal / ITO stack design, employing the ITO dielectric layer as a stress buffer layer to effectively release residual interfacial stress. In particular, when the opaque electrode is used as the bottom electrode, it fundamentally eliminates the phenomenon of metal film peeling or edge chipping caused by shear force concentration during the P4 edge cleaning process, thereby improving the component yield and long-term operational reliability.
[0019] 4. An ITO / metal / ITO composite electrode structure is adopted in the opaque electrode to achieve a decoupling design between the high conductivity metal core and the functional dielectric surface. This structure allows the use of low-cost, high conductivity metals such as copper and silver as intermediate conductive layers. The upper and lower ITO layers not only play a role in chemical barrier and anti-oxidation protection, but also serve as transition layers to improve the bandgap matching and contact characteristics with adjacent semiconductor layers, thus balancing the electrical transmission performance, environmental stability and manufacturing cost of the electrode.
[0020] 5. Light enters from the top transparent electrode (pure ITO) and is reflected by the bottom high-reflectivity composite electrode to achieve optical path gain, thereby increasing the generation probability of photogenerated carriers. Combined with the aforementioned improvement in electrical performance brought about by eliminating the interface oxide layer and reducing series resistance, this structure has a synergistic enhancement effect in optical management and electrical transmission, which plays a positive role in improving the photoelectric conversion efficiency of the component. Attached Figure Description
[0021] Figure 1 This is a structural schematic diagram of Example 1;
[0022] Figure 2 This is a schematic diagram of the scribing process for steps P1 to P3;
[0023] Figure 3 These are optical microscope images of P1~P3 after scribing in Example 1 (top left) and Comparative Example 1 (top right), and physical photographs of Example 1 (bottom left) and Comparative Example 1 (bottom right).
[0024] Figure 4 This is a comparison chart of the component stability data between Example 1 and Comparative Example 1;
[0025] The component names represented by each number in the diagram are as follows:
[0026] 1-Substrate, 2-First electrode, 3-First charge transport layer, 4-Perovskite absorber layer, 5-Second charge transport layer, 6-Second electrode. Detailed Implementation
[0027] The present invention will be further explained and described below with reference to the accompanying drawings.
[0028] This specific embodiment is merely an explanation of the present invention and is not intended to limit the invention. Any changes made by those skilled in the art after reading this specification, as long as they fall within the scope of the claims, will be protected by patent law.
[0029] Example 1
[0030] This embodiment provides a high-conversion-efficiency perovskite solar cell module, which is a positively mounted PVK module. For example... Figure 1As shown, the solar cell module includes, from bottom to top, a substrate 1, a first electrode 2, a first charge transport layer 3, a perovskite absorber layer 4, a second charge transport layer 5, and a second electrode 6.
[0031] Specifically, substrate 1 is a rigid glass substrate. First electrode 2 is an opaque positive electrode, its structure comprising a first ITO transparent layer, a metal layer, and a second ITO transparent layer, the metal layer being disposed between the two ITO transparent layers; more specifically, the metal is copper. First charge transport layer 3 is a hole transport layer. Second charge transport layer 5 is an electron transport layer. Second electrode 6 is a transparent negative electrode, specifically ITO.
[0032] More specifically, the first electrode 2 (positive electrode, bottom electrode) has a structure of 50nm ITO + 80nm Cu + 50nm ITO, and the second electrode 6 (negative electrode, top electrode) has a structure of 100nm ITO. Both are DC sputtered, with a target-substrate distance of 8cm and a bottom pressure ≤5E-4Pa. The ITO sputtering power is 1.72KW, the coating gas pressure is 0.4Pa, the oxygen ratio is 2.5%@total gas flow rate is 150sccm, and the coating rate is 0.5nm / s; the Cu sputtering power is 1.85KW, the coating gas pressure is 0.35Pa, and the coating rate is 0.3nm / s.
[0033] Specifically, such as Figure 2 As shown, the fabrication process of the above-mentioned high-conversion-efficiency perovskite solar cell module is as follows:
[0034] 1) Clean a 6*6cm transparent glass substrate in an ultrasonic bath for 15 minutes in the order of glass cleaner, deionized water, and ethanol, and then dry it with a nitrogen gun for later use.
[0035] 2) Depositing sandwich electrodes on a transparent glass substrate; First, the dried glass substrate is treated in a UV ozone generator for 30 minutes, and then a physical vapor deposition (PVD) process is used to deposit sandwich electrodes on a 1×10⁻⁶ substrate. -4 A composite electrode was obtained by vacuum deposition of 50nm ITO + 80nm Cu + 50nm ITO; laser P1 was used to scribing the glass surface to determine the width of the sub-cell.
[0036] 3) Preparation of hole transport layer on sandwich electrode: On the substrate surface on which sandwich electrode has been deposited, a thin film of nickel oxide (NiOx) with a thickness of about 15 nanometers is formed by physical vapor deposition (PVD) process, and then immediately transferred into a glove box filled with N2 to obtain hole transport layer.
[0037] 4) Preparing a perovskite layer on the hole transport layer; dissolving lead iodide, formamidine iodide, and cesium iodide in a molar ratio of 1:(0.8~0.95):(0.05~0.2) in a solution composed of N,N-dimethylformamide and N-methyl-2-pyrrolidone in a volume ratio of (4~6):(1~1.5) to prepare a precursor solution; stirring the precursor solution at room temperature for 2~5 hours to obtain the perovskite precursor material. The precursor solution concentration was 0.9–1.5 mmol. The perovskite precursor solution was deposited onto the substrate via slit coating and annealed at 100–150 °C for 20 min to obtain a dense and uniform film with a thickness of approximately 500 nm. More specifically, in this embodiment, the molar ratio of lead iodide, formamidinium iodide, and cesium iodide was 1:0.9:1; the volume ratio of N,N-dimethylformamide and N-methyl-2-pyrrolidone was 5:1.2; the precursor solution was stirred for approximately 3 h; the precursor solution concentration was 1.2 mmol; and the annealing program was 120 °C for 15 min.
[0038] 5) Fabricate an electron transport layer on the perovskite light-absorbing layer; in a 1×10 -4 Pa vacuum deposition of C60 with a thickness of 15-25 nm, followed by atomic layer deposition of SnO2 with a thickness of 10-20 nm; to obtain a composite electron transport layer; laser P2 scribing onto the ITO surface to form a series channel; in this embodiment, the C60 thickness is 20 nm and the SnO2 thickness is 15 nm.
[0039] 6) Finally, a transparent electrode layer is fabricated on the electron transport layer; in a 1×10 -4 A 100 nm ITO layer was deposited in vacuum using Pa to obtain a transparent electrode. Lasers P3 and P4 were used to connect sub-cells in series and clean the edges, respectively, thus completing the fabrication of the perovskite solar cell.
[0040] The results are as follows Figure 3 As shown on the left, the effective area of the component is defined as 18.4 cm² using a mask. 2 During the test, light was incident from the ITO side.
[0041] Comparative Example 1
[0042] This comparative example provides a perovskite solar cell module. From bottom to top, it includes a rigid glass substrate, a transparent ITO positive electrode, a hole transport layer, a perovskite absorber layer, an electron transport layer, and an opaque negative electrode.
[0043] The transparent ITO positive electrode is the bottom electrode.
[0044] The opaque negative electrode is the top electrode, with a structure of 50nm ITO + 80nm Cu + 50nm ITO.
[0045] All sputtering methods were performed using DC sputtering with a target-substrate distance of 8 cm and a base pressure of ≤5E-4 Pa. The ITO sputtering power was 1.72 kW, the coating gas pressure was 0.4 Pa, the oxygen ratio was 2.5% @ a total gas flow rate of 150 sccm, and the coating rate was 0.5 nm / s. The Cu sputtering power was 1.85 kW, the coating gas pressure was 0.35 Pa, and the coating rate was 0.3 nm / s.
[0046] Specifically, such as Figure 2 As shown, the fabrication process of the above-mentioned perovskite solar cell module is as follows:
[0047] 1) Clean a 6*6cm transparent glass substrate in an ultrasonic bath for 15 minutes in the order of glass cleaner, deionized water, and ethanol, and then dry it with a nitrogen gun for later use.
[0048] 2) Deposition of transparent electrodes on transparent glass substrates; First, the dried glass substrate is treated in an ultraviolet ozone generator for 30 minutes, and then a transparent electrode is deposited on a 1×10⁻⁶ transparent glass substrate using a physical vapor deposition (PVD) process. -4 A transparent electrode was obtained by vacuum deposition of 100 nm ITO using Pa; laser P1 was used to scribing the glass surface to determine the width of the sub-cell.
[0049] 3) Preparation of hole transport layer on conductive substrate: First, a transparent conductive substrate with ITO deposited is placed in an ultraviolet ozone generator for 30 minutes. Then, a nickel oxide (NiOx) thin film with a thickness of about 15 nanometers is deposited on the substrate surface by physical vapor deposition (PVD). Then, it is immediately transferred to a glove box filled with N2 to obtain hole transport layer.
[0050] 4) Preparing a perovskite layer on the hole transport layer; dissolving lead iodide, formamidine iodide, and cesium iodide in a molar ratio of 1:(0.8~0.95):(0.05~0.2) in a solution composed of N,N-dimethylformamide and N-methyl-2-pyrrolidone in a volume ratio of (4~6):(1~1.5) to prepare a precursor solution; stirring the precursor solution at room temperature for 2~5 hours to obtain the perovskite precursor material. The precursor solution concentration was 0.9–1.5 mmol. The perovskite precursor solution was deposited onto the substrate via slit coating and annealed at 100–150 °C for 20 min to obtain a dense and uniform film with a thickness of approximately 500 nm. More specifically, in this comparative example, the molar ratio of lead iodide, formamidinium iodide, and cesium iodide was 1:0.9:1; the volume ratio of N,N-dimethylformamide and N-methyl-2-pyrrolidone was 5:1.2; the precursor solution was stirred for approximately 3 h; the precursor solution concentration was 1.2 mmol; and the annealing program was 120 °C for 15 min.
[0051] 5) Fabricate an electron transport layer on the perovskite light-absorbing layer; in a 1×10 -4Pa vacuum deposition of C60 with a thickness of 15-25 nm, followed by atomic layer deposition of SnO2 with a thickness of 10-20 nm, yields a composite electron transport layer. Laser P2 scribing is then applied to the ITO surface to form tandem channels; in this comparative example, the C60 thickness is 20 nm and the SnO2 thickness is 15 nm.
[0052] 6) Finally, a transparent electrode layer is fabricated on the electron transport layer; in a 1×10 -4 A composite electrode was obtained by vacuum deposition of 50 nm ITO + 80 nm Cu + 50 nm ITO. Lasers P3 and P4 were used to complete the series connection and edge cleaning of sub-cells, respectively, to complete the fabrication of perovskite solar cells.
[0053] The results are as follows Figure 3 As shown on the right, the effective area of the component is defined as 18.4 cm² using a mask. 2 .
[0054] The relevant performance of Example 1 and Comparative Example 1 was tested under standard test conditions through three repeated experiments. The results are as follows: Figure 4 As shown in Table 1.
[0055] Table 1. Component efficiency of the comparative and embodiment examples.
[0056] Comparative Example 6.2306.4666.262 14.89617.79817.438 58.46567.36369.551 4.0904.0864.004 Example 6.7306.736 6.812 21.24521.04421.260 78.42579.01277.638 4.0254.0214.029
[0057] As can be seen from the data in Table 1:
[0058] 1. The VOC of the embodiment (6.730~6.812 V) is significantly higher than that of the comparative example (6.230~6.466 V), indicating that the open-circuit voltage of the battery in the embodiment is more stable and higher overall, which may be related to reduced interface recombination, reduced contact resistance or improved energy level matching.
[0059] 2. The FF of the embodiment is 77.6%~79.0%, while that of the comparative example is 58.5%~69.6%. The improvement of FF usually means a reduction in series resistance, an increase in parallel resistance, and more efficient charge extraction, which is directly related to the improvements mentioned above, such as "avoiding CuO from increasing contact resistance and reducing P3 thermal damage";
[0060] 3. The PCE of the example was 21.04%~21.26%, while that of the comparative example was 14.90%~17.80%. The efficiency improvement mainly came from the combined improvement of VOC and FF, while the JSC did not change much (~4.0 mA / cm²), indicating that optical absorption or photocurrent collection was not significantly affected, and the improvement was more in electrical performance and stability.
[0061] 4. JSC showed almost no difference between the comparative example and the embodiment (approximately 4.02~4.09 mA / cm²), indicating that the light absorption and carrier generation of the two structures were similar, further confirming that the efficiency improvement did not come from light management, but from the reduction of electrical losses (series resistance, recombination, contact, etc.).
[0062] 5. The three sets of data in the example showed smaller fluctuations (VOC: 6.73~6.81; FF: 77.6~79.0; PCE: 21.04~21.26), while the comparative example showed larger fluctuations (especially FF and PCE), indicating that the electrode structure / laser process used helps to improve the repeatability of component performance and process stability.
[0063] In summary, compared with the comparative example, the perovskite solar modules of the present invention show significant improvements in VOC, FF and PCE, while JSC remains basically unchanged. This indicates that the efficiency improvement mainly comes from the reduction of electrical losses and the improvement of charge extraction / contact performance. At the same time, the consistency and stability of module performance are also better.
Claims
1. A perovskite solar cell module, comprising a substrate (1), a first electrode (2), a first charge transport layer (3), a perovskite absorber layer (4), a second charge transport layer (5), and a second electrode (6) stacked sequentially, characterized in that: The first electrode (2) and the second electrode (6) have opposite polarities; one of the first electrode (2) and the second electrode (6) is a transparent electrode and the other is an opaque electrode; the first charge transport layer (3) is an electron transport layer or a hole transport layer that matches the work function of the first electrode (2); the second charge transport layer (5) is an electron transport layer or a hole transport layer that matches the work function of the second electrode (6); The transparent electrode is an ITO electrode; the opaque electrode is a composite electrode, comprising a first ITO transparent layer, a metal layer, and a second ITO transparent layer, wherein the metal layer is disposed between the two ITO transparent layers. The metal layer is made of silver or copper; Furthermore, during the fabrication of the perovskite solar cell module, the opaque electrode is set as the bottom electrode and the transparent electrode is set as the top electrode to avoid ablation of the metal layer during the P3 scribing process.
2. The perovskite solar cell module according to claim 1, characterized in that: The thickness of the first ITO transparent layer and the second ITO transparent layer is 20~50nm, and the thickness of the metal layer is 50~100nm.
3. The perovskite solar cell module according to claim 1, characterized in that: The first electrode (2) is an opaque positive electrode; the first charge transport layer (3) is a hole transport layer; the second electrode (6) is a transparent negative electrode; the second charge transport layer (5) is an electron transport layer; when in use, light is incident from the side of the second electrode (6).
4. A perovskite solar cell module according to claim 1, characterized in that: The substrate (1) is a transparent substrate; the first electrode (2) is a transparent negative electrode; the first charge transport layer (3) is an electron transport layer; the second electrode (6) is an opaque positive electrode; the second charge transport layer (5) is a hole transport layer; when in use, light is incident from the transparent substrate side.
5. A perovskite solar cell module according to claim 1, characterized in that: The first electrode (2) is an opaque negative electrode; the first charge transport layer (3) is an electron transport layer; the second electrode (6) is a transparent positive electrode; the second charge transport layer (5) is a hole transport layer; when in use, light is incident from the side of the second electrode (6).
6. A perovskite solar cell module according to claim 1, characterized in that: The substrate (1) is a transparent substrate; the first electrode (2) is a transparent positive electrode; the first charge transport layer (3) is a hole transport layer; the second electrode (6) is an opaque negative electrode; the second charge transport layer (5) is an electron transport layer; when in use, light is incident from the transparent substrate side.
Citation Information
Patent Citations
Method for fabricating a solar module, sub-laminate for fabricating a solar module and solar module
EP3453059A1